High Tatras forest structure changes and their influence on rain interception and some components of water balance - KŇAVA, K.; NOVÁK, Viliam; ORFÁNUS, T.; MAJERČÁK, J. (Contributions to Geophysics and Geodesy, 2008)
This paper contains results of quantitative analysis of the influence of intercepted water by different canopies (grass, coniferous forest) with different LAI (leaf area index) characteristics on water balance structure of the soil – plant - atmosphere continuum (SPAC) and especially on soil water movement in soil root zone. Site FIRE near Starý Smokovec in Vysoké Tatry (High Tatras) Slovakia, as a part of the area cleared by windthrow in 2004 was used for the analysis. Simulation model GLOBAL was used as a tool for soil water movement calculation. The summer season (April 1 – October 31, 2006) was used for the simulation. Results of water movement in SPAC demonstrate the importance of canopy changes on the structure of soil water balance and on soil water content of the root zone of soil.